Analysis of Metal Fe at Algae Eucheuma cottoni in Region of Baubau Coastal - Muhammad Tasjiddin Teheni (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2020)
Abstract. Eucheuma cottoni (called algae) is one of plant that usefull for human life as well as alternative energy, bioaccumulation of metal in waters, food, fertilizer and also in health. This study aims to determine the level of Fe ions in Eucheuma cottoni in the region of Baubau coastal. The concentration of Fe metal was determined by atomic absorption spectrophotometer (AAS) which destructing process was done by HNO3 concentrated. The results showed that the highest and lowest level of Fe available on Lowu-Lowu and Palabusa village which value of 0.4885 and 0.0498 ppm, respectivelly. The high concentration of Fe metal expecially in Lowu-lowu had been passed the specific threshold. The monitoring of heavy metal pollution in Baubau coastal necessary to be done in the aquatic environment so it can be maximize the quality and production of seaweed